Improving Highway Work Zone Mobility in the Developing World: A Systematic Literature Review of Work Zone Delay Measures and Technological Solutions - Ansari F.A.; Pani A.; Mohapatra S.S. (My University, 2025)
Work zones have long been cited as a significant cause of road fatalities and traffic delays, with evident negative impacts on traffic safety and mobility. This review outlines the mobility measures reported in the work zone delay context in three thrusts: 1) work zone travel delay, 2) queueing length, and 3) user cost. Through a critical comparison of reported findings, the current review illuminates the possibilities of more guided research that would expedite the goal of achieving an optimal work zone layout with minimal fatalities, maximum mobility, and efficiency. Additionally, we expanded our review to include other engineering disciplines to identify potential technologies that could be used to make work zones smarter. Finally, policy interventions necessary to improve the safety and mobility of work zones are discussed, followed by a critical discussion of the way forward. © The Author(s) 2024.